2023
DOI: 10.1021/acs.molpharmaceut.3c00440
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Determinants for the Viscosity of Concentrated Monoclonal Antibody Solutions

Ilaria Mosca,
Kévin Pounot,
Christian Beck
et al.

Abstract: Monoclonal antibodies (mAbs) are particularly relevant for therapeutics due to their high specificity and versatility, and mAb-based drugs are hence used to treat numerous diseases. The increased patient compliance of self-administration motivates the formulation of products for subcutaneous (SC) administration. The associated challenge is to formulate highly concentrated antibody solutions to achieve a significant therapeutic effect, while limiting their viscosity and preserving their physicochemical stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 122 publications
1
1
0
Order By: Relevance
“…Given the complex charge-variant profile of FP-1 discussed above, we posit that the asymmetric surface charge on the diabody and the IL-22 domains result in attractive long-range electrostatic interactions between surfaces with complementary charge distribution. This is consistent with previously reported results, demonstrating the role of electrostatic interactions in driving self-association and high viscosity in mAbs via cluster formation . Once in close proximity, short-range hydrophobic interactions become entropically favored and can lead to the formation of FP-1 dimers via the solvent-exposed loops of the V L domain.…”
Section: Discussionsupporting
confidence: 93%
“…Given the complex charge-variant profile of FP-1 discussed above, we posit that the asymmetric surface charge on the diabody and the IL-22 domains result in attractive long-range electrostatic interactions between surfaces with complementary charge distribution. This is consistent with previously reported results, demonstrating the role of electrostatic interactions in driving self-association and high viscosity in mAbs via cluster formation . Once in close proximity, short-range hydrophobic interactions become entropically favored and can lead to the formation of FP-1 dimers via the solvent-exposed loops of the V L domain.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is in good agreement with known data; it was previously shown that the minimum IgG concentration detectable with viscometry is ~0.1 mg/mL [38]. It should be noted that the viscosity of colloids depends not only on concentration, but also on temperature [39], pH [40], ionic strength, cation-anion environment [41], and the like [42][43][44]. Progress in viscometry research can be found in a literature review [45].…”
Section: Study Of the Physicochemical Properties Of Aqueous Igg Collo...supporting
confidence: 90%
“…To this end, overcoming the often steep viscosity increase as a function of concentration is key to fitting the dose into a pen injector. Mosca et al provided key insights into the biophysical root causes of this phenomenon in this article series.…”
mentioning
confidence: 99%